2014
DOI: 10.1186/1546-0096-12-27
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional electromyography assessment in linear scleroderma patients

Abstract: BackgroundMuscle atrophy and asymmetric extremity growth is a common feature of linear scleroderma (LS). Extra-cutaneous features are also common and primary neurologic involvement, with sympathetic dysfunction, may have a pathogenic role in subcutaneous and muscle atrophy. The aim was investigate nerve conduction and muscle involvement by electromyography in pediatric patients with LS.MethodsWe conducted a retrospective review of LS pediatric patients who had regular follow up at a single pediatric center fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
6
0
2
Order By: Relevance
“…5 In our study, segmental vitiligo was found to affect younger age group which is comparable with the studies by Van et al and Ratnam et al 6,7 A female preponderance was observed in our study of Linear Dermatoses. This finding in our study in patients with linear morphea correlated with the study by Claudia Saad et al and Mukhapadhyay et al 8,9 With Lichen striatus a similar female preponderance was observed in our study. This is similar to Kerstin T Abagge et al who observed a female: male ratio of 3: 1.10…”
Section: Age and Gendersupporting
confidence: 93%
“…5 In our study, segmental vitiligo was found to affect younger age group which is comparable with the studies by Van et al and Ratnam et al 6,7 A female preponderance was observed in our study of Linear Dermatoses. This finding in our study in patients with linear morphea correlated with the study by Claudia Saad et al and Mukhapadhyay et al 8,9 With Lichen striatus a similar female preponderance was observed in our study. This is similar to Kerstin T Abagge et al who observed a female: male ratio of 3: 1.10…”
Section: Age and Gendersupporting
confidence: 93%
“…One theory suggests that adipose tissue and muscle atrophy in linear scleroderma is caused by sympathetic nervous system disorders, and there has been exhaustive investigation on the muscle and nerve lesions that are found in this disease. Saad Magalhaes et al 126 evaluated electromyograms for nine patients with juvenile linear scleroderma (linear scleroderma/ limbs, n = 7; Parry-Romberg syndrome, n = 2) and found myogenic changes in the muscle underlying the lesions in eight patients (both patients with Parry-Romberg syndrome had myogenic changes in the masticatory muscles), while one patient had neurogenic changes. In an investigation on the conduction velocity of limb motor neurons and sensory nerves, they reported that they found abnormalities in a patient with linear scleroderma in whom a lesion extended deep into the thigh.…”
Section: Cq17 Is Phototherapy Effective For Treating Skin Lesions?mentioning
confidence: 99%
“…Therefore, their clinical manifestations were different from those of our patient, who had widespread muscle weakness. Because central and peripheral nerve involvement is frequently seen in localized scleroderma, we speculate that linear scleroderma may occasionally present with neurogenic muscle weakness independent of skin lesions, as in the one case described by Magalhães et al It remains unknown whether muscle findings in linear scleroderma differ according to the presence or absence of PRS.…”
Section: Discussionmentioning
confidence: 70%
“…Few studies have examined EMG in patients with liner scleroderma or PRS. Only one report examined needle EMG in a series of patients with linear scleroderma, including two PRS cases . In that study, eight of nine pediatric patients with linear scleroderma, including two with concomitant PRS, showed a myogenic pattern in the muscles underlying the extremity skin lesions on needle EMG; the remaining one patient with linear scleroderma alone had a neurogenic pattern.…”
Section: Discussionmentioning
confidence: 99%